Adoption of IFRS 8 on Borsa Istanbul listed companies and its effects on earnings management - Külah, Sezer (My University, 2021)
Bu çalışmanın amacı, UFRS 8'i ve Kazanç Yönetimi Üzerindeki Etkilerini ve değer ilişkisini araştırmaktır. Konuyu araştırmak için 2005-2020 yılları arasında seçilen toplam 22 Borsa İstanbul şirketine dayalı bir veri seti değerlendirilmiştir. Stata programında panel veri analizi kullanılarak toplam 291 firma yılı gözlemi ve iki model çalıştırılmıştır. Elde edilen sonuçlara göre, hisse başına öz sermayenin defter değeri ile hisse başına kazanç arasında hisse senedi fiyatları üzerinden pozitif bir ilişki vardır. Ayrıca, UFRS 8'i benimseyen şirketler için faaliyet bölümlerinin hisse başına kazanç ve hisse başına defter değerinin hisse senedi fiyatları üzerinde olumlu etkisi bulunmaktadır. Bu çalışmada ilk bölümde literatür özetlenmiştir. İkinci bölümde, UFRS 8'i benimseyen şirketler üzerinde değer ilişkisi analizleri yapılmıştır. Son bölümde UFRS 8 uygulayan şirketlerle kazanç yönetimi ilişkisi incelenmiştir. Firmaların kazançlarında artış göstermeye daha istekli oldukları sonucuna varılmıştır.

The purpose of this study is to investigate the IFRS 8 and its effects on Earnings Management and value relevance. To investigate the issue a dataset based on a total of 22 selected Borsa Istanbul companies are evaluated from the years 2005 to 2020. A total of 291 firm year observations and two models are run using panel data analysis on the Stata program. According to the results, there is a positive relation between the book value of equity per share and earnings per share over stock prices. Furthermore, earnings per share of segments and the book value of equity per share have a positive effect on stock prices for the companies that have applied Operating Segments Standard. In this study, literature is summarized in the first part. In the second part, value relevance analyses are carried out over the companies that have adopted IFRS 8. In the last section, the relationship between earnings management and companies applying IFRS 8 is examined. It is concluded that firms are more willing to show an increase in their earnings.
Keywords: Business; Değer İlişkisi IFRS; Earnings Management; Faaliyet Bölümleri; IFRS 8; İşletme; Kazanç Yönetimi; Operating Segments; UFRS; UFRS 8; Value Relevance